(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This article argues that postcolonial concepts of hybridity, Orientalism and the subaltern can provide a hermeneutic starting point for interpretation of Jelena Dimitrijevic’s novel The New Women, a Serbian modernist female fiction representing life of women in the affluent Ottoman circles in Thessalonica at the end of the 19th, the beginning of the 20th century. Half of the article is a theoretical introduction into three concepts and their wider theoretical implications. The other half deals with the novel itself and all its inherent paradoxes, aspiring to show Jelena Dimitrijevic’s proto-theoretical awareness of these problems avant la lettre, long before they were conceptualized by Edward Said, Homi Bhabha and Gayatri Chakravorty Spivak. Both the theoretical introduction and the interpretation touch upon the problem of Maria Todorova’s concept of Balkanism as well.